My first encyclopedia of human body - Dr.Ahmad Sultan (Karachi: Children Publications, 2012)
This encyclopedia is a simple introduction to the miracle of the human body. With stimulating design and easy-to-read text, this book will enable children to make sense of the body.
Keywords: Human Body; Scientific concepts